Microplastic abundance, distribution and composition in the Pearl River along Guangzhou city and Pearl River estuary, China. (February 2019) - Yan, Muting; Nie, Huayue; Xu, Kaihang; He, Yuhui; Hu, Yingtong; Huang, Yumei; Wang, Jun
Abstract: Like many urban rivers, the Pearl River in China is contaminated with microplastics. Compared with marine environments, microplastic pollution in freshwater is less understood, especially in urban rivers. In the present study, the abundance and distribution of microplastics in water from the Pearl River was investigated, including the estuary and the urban section along Guangzhou. The average abundance of microplastics was 19, 860 items/m 3 and 8902 items/m 3 in the urban section and estuary, respectively. Wastewater effluents from cities might be a main source of microplastics in the Pearl River, and the urban tributaries might act as retention systems for microplastics. Among these microplastics, over 80% of them were less than 0.5 mm. The main shapes of microplastics were film, fragment, and fiber, mostly blue or transparent. Moreover, the most common polymer types of these microplastics were polyamide (26.2%) and cellophane (23.1%). This study reveals the contamination and characteristics of microplastics in the Pearl River, and provides important data for further research on microplastics in freshwater ecosystems. Graphical abstract: Highlights: First comparison of microplastics between estuary and urban section of the Pearl River. Films were the main shape in the Pearl River. PA and cellophane were the dominant polymer types in the Pearl River. Waste water effluents from urban city might be a main source of microplastics.